Incidental finding of mutation in the HBB gene associated with heterozygous β-thalassemia in adolescent pregnant (Research, Society and Development, 2024)
Introduction: The coexistence of hemoglobinopathy C and β-thalassemia poses significant diagnostic and therapeutic challenges, given the complexity of these conditions characterized by beta-globin deficiency, which can lead to hemolytic anemia, splenomegaly, and microcytosis, emphasizing the importance of early diagnosis to prevent complications. The objective of the study is to present the case of hemoglobinopathy C associated with β-thalassemia in an adolescent pregnant woman and describe the pathologies found, taking into account the current epidemiology. Methodology: A descriptive cross-sectional study was conducted, which included relevant literature review and analysis of clinical data. Case report: The case of a 16-year-old patient at 30.5 weeks of gestation is described in depth, who during pregnancy experienced complications such as oligohydramnios, preterm birth, and preeclampsia, and was treated with red blood cell transfusions. Discussion: The clinical and therapeutic implications of the coexistence of these two hemoglobinopathies in pregnancy are extensively discussed, as well as the recommended management and follow-up strategies to improve maternal and fetal health. Conclusion: Emphasis is placed on the importance of a comprehensive and accessible approach for the adequate management of these pathologies during pregnancy, as well as for addressing potential complications and improving perinatal outcomes.